Os Efeitos da aprendizagem colaborativa no ensino de leitura e compreensão textual em língua portuguesa - (:unkn) unknown (Universidade Estadual de Goiás, 2014)
The dissertation on screen is the report of research carried out in order to contribute to questioning the teaching of reading in a social interactionist perspective. The cutting was made base on data collected in a public school located in the eastern region of Goiania city, Goiás. The people who had participation in the management and educational research was the coordinator of the school, the class teacher of sixth grade (6th) as well as the students in this class. For this work we adopted the qualitative research, which constitute a observation work with the realization of documentary analysis, semi-structured interview and application of practical lessons in reading and textual comprehension of the collaborative learning. Some moments of the collaboration shared by students were recorded in audio an subsequently transcribed, with the purpose of data analysis. Based on the vigotskian assumptions that learning happens, firstly, interpsychological or interpersonal manner and secondly intrapsychological or intrapersonal form (Vygotsky, 1998), the research aimed to observe the effects of collaborative learning in the classroom reading in Portuguese as their mother tongue and to analyze the importance of group interaction in the development of reading skills on participating students.
Keywords: Ensino de leitura; Aprendizagem colaborativa; Estratégias - Leitura; Interação em grupos; Teaching of reading; Learning colaborative; Strategiges - Reading; Interct in groups; CIENCIAS HUMANAS::EDUCACAO